Implementasi Kombinasi Jaringan Syaraf Tiruan Metode Self-Organized Map (SOM) dan Bidirectional Associative Memory (BAM) Pada AI Game Action Adventure - Kevin Leonard Tjung; Gregorius Satia Budhi; Kristo Radion Purba (Jurnal Infra, 2017)
Game is a multi media application that need some main parts such as, goal, challenge and game play or usually has been know as rules in a game.Action adventure game will apply real time system in its game play. Real time game usually needs fast decision making method for artificial intelligence, so it can’t interrupt any system in the game.Self-Organized Map (SOM) and Bidirectional Associative Memory (BAM) is one of the fastest method that can be used to process data for decision making and for adaptation. SOM method can be used as decision making part for AI while BAM can be use to store player last move that being used to kill the AI.Based on testing result, SOM and BAM can be applied in real time game system as AI and successfully adapt to player attacks although not perfect.